Wheat curl mite, Aceria tosichella, and transmitted viruses: an expanding pest complex affecting cereal crops - Navia, Denise; Mendonça, Renata Santos de; Skoracka, Anna; Szydło, Wiktoria; Knihinicki, Danuta; Hein, Gary L.; Pereira, Paulo Roberto Valle da Silva; Truol, Graciela Ana Maria; Lau, Douglas (Springer, 2018)
The wheat curl mite (WCM), Aceria tosichella, and the plant viruses it transmits represent an invasive mite-virus complex that has affected cereal crops worldwide. The main damage caused by WCM comes from its ability to transmit and spread multiple damaging viruses to cereal crops, with Wheat streak mosaic virus (WSMV) and Wheat mosaic virus (WMoV) being the most important. Although WCM and transmitted viruses have been of concern to cereal growers and researchers for at least six decades, they continue to represent a challenge. In older affected areas, for example in North America, this mite-virus complex still has significant economic impact. In Australia and South America, where this problem has only emerged in the last decade, it represents a new threat to winter cereal production. The difficulties encountered in making progress towards managing WCM and its transmitted viruses stem from the complexity of the pathosystem. The most effective methods for minimizing losses from WCM transmitted viruses in cereal crops have previously focused on cultural and plant resistance methods. This paper brings together information on biological and ecological aspects of WCM, including its taxonomic status, occurrence, host plant range, damage symptoms and economic impact. Information about the main viruses transmitted by WCM is also included and the epidemiological relationships involved in this vectored complex of viruses are also addressed. Management strategies that have been directed at this mite-virus complex are presented, including plant resistance, its history, difficulties and advances. Current research perspectives to address this invasive mite-virus complex and minimize cereal crop losses worldwide are also discussed.